The pleasant nights. - Straparola, Giovanni Francesco, approximately 1480-1557? (Lorenzo da Ponte Italian library series., 2012)
Immensely entertaining and readable, The Pleasant Nights will appeal to anyone interested in fairy tales, ancient stories, and folk creations.